Neuroanatomical basis of the nerve growth factor ovulation–induction pathway in llamas. Issue 3 (17th December 2020) - Carrasco, Rodrigo A; Singh, Jaswant; Ratto, Marcelo H; Adams, Gregg P
Abstract: The objective of the study was to characterize the anatomical framework and sites of action of the nerve growth factor (NGF)-mediated ovulation-inducing system of llamas. The expression patterns of NGF and its receptors in the hypothalamus of llamas ( n  = 5) were examined using single and double immunohistochemistry/immunofluorescence. We also compare the expression pattern of the P75 receptor in the hypothalamus of llama and a spontaneous ovulator species (sheep, n  = 5). Both NGF receptors (TrkA and P75) were highly expressed in the medial septum and diagonal band of Broca, and populations of TrkA cells were observed in the periventricular and dorsal hypothalamus. Unexpectedly, we found NGF immunoreactive cell bodies with widespread distribution in the hypothalamus but not in areas endowed with NGF receptors. The organum vasculosum of the lamina terminalis (OVLT) and the median eminence displayed immunoreactivity for P75. Double immunofluorescence using vimentin, a marker of tanycytes, confirmed that tanycytes were immunoreactive to P75 in the median eminence and in the OVLT. Additionally, tanycytes were in close association with GnRH and kisspeptin in the arcuate nucleus and median eminence of llamas. The choroid plexus of llamas contained TrkA and NGF immunoreactivity but no P75 immunoreactivity. Results of the present study demonstrate sites of action of NGF in the llama hypothalamus, providing support for the hypothesis of a central effect of NGF in the ovulation-inducing mechanism in llamas. Abstract : Hypothalamic pathways for NGF actions in camelids.